Respon Pertumbuhan Tanaman Bawang Merah Akibat Pemberian Pupuk Organik Cair Limbah Pasar - Miradiani, Kayla; Rahmi, Hayatul; Sugiono, Darso (JURNAL AGROPLASMA, 2023)
Shallot (Allium ascalonicum L.) is a horticultural commodity that requires adequate nutrition during its growth. Nutritional needs can be met through fertilization. The use of organic fertilizers is an environmentally friendly fertilization option in an effort to reduce the introduction of inorganic fertilizers into the soil. The purpose of this study was to obtain market waste liquid organic fertilizer concentration that can support the growth of shallots. The research was conducted from January 2023 to March 2023 at Ciherang Land, Wadas Village, and Karawang Regency. The single factor study used a randomized block design (RBD) consisting of 8 treatments which were repeated 5 times so that 40 experimental plots were obtained with the following treatments: P0 (Concentration 0 ml/l); P1 (Concentration 100 ml/l); P2 (Concentration 200 ml/l); P3 (Concentration 300 ml/l); P4 (Concentration 400 ml/l); P5 (Concentration 500 ml/l); P6 (Nasa POC Concentration 5 ml/l); P7 (NPK Fertilizer 500 kg/ha). The results showed that the concentration of liquid organic fertilizer from market waste had a significant effect on shallot plant height with the treatment P7 (NPK Fertilizer 500 kg/ha) giving the best plant height of 43.00 cm at 42 dap.Â Keywords: Liquid Organic Fertilizer, Horticulture, Shallot